The changing distribution of earnings in OECD countries - Atkinson, A. B. (Anthony Barnes), 1944- (Oxford : Oxford University Press, 2008)
Examining what people are paid and how pay differences have changed over time, this title presents new theories that challenge thinking on the impact of education, technology globalization and the rigidity of labour markets.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Income distribution -- OECD countries; Income distribution -- OECD countries -- Econometric models; Wage differentials -- OECD countries